Composite membranes with nanofilms assembled on nanofiber supports for high-performance nanofiltration with antibacterial property. (April 2022) - Xia, Jingjing; Lv, Yan; Sun, Rui; Meng, Lijun; Liu, Tianxi
Abstract: Nanofiltration has been widely applied in the field of desalination, wastewater treatment and water softening as an emerging and promising membrane separation technology. In order to break the trade-off effect between selectivity and permeability, we develop a novel thin-film composite nanofiltration membrane via a one-step interfacial assembly strategy of PDA/PEI nanofilms on nanofiber substrates. The ultrathin PDA/PEI nanofilm is defect-free, acting as the selective layer for ion sieving. The nanofiber substrate with high porosity provides plenty of mass transfer channels to reduce the membrane resistance, resulting in a enhanced water permeability of 18.1 L m -2  h -1 bar -1, which is 3 times higher than that prepared with commercial substrates. Attributed to the universally adhesive property of PDA, the PDA/PEI nanofilm can well integrate with the nanofiber substrate, enhancing the interfacial interaction strength and thus the composite structure stability. As a versatile platform, the abundant Ag nanoparticles are immobilized onto the PDA/PEI nanofilm surface, endowing the membrane with significant antibacterial property. This is of importance for membrane antifouling during the long-term and practical applications. This work could pave a facile way to develop advanced nanofiltration membranes with outstanding separation performance and various functions. Graphical abstract: Image 1 Highlights: A novel TFC nanofiltration membrane is developed via a one-step interfacial assembly strategy on a nanofiber substrate. The ultrathin PDA/PEI nanofilm is defect-free and positively charged, acting as a selective layer for ion sieving. The nanofiber substrate results in relatively high water permeability by reducing the membrane resistance. Ag nanoparticles are immobilized onto the nanofilm surface to endow the membrane with significant antibacterial property. AgNPs are immobilized onto the PDA/PEI nanofilm surface to endow the membrane with significant antibacterial property.